PARTS OF SPEECH THAT ARE NOT GRAMMATICALLY RELATED TO PARTS OF SPEECH. (Conference Zone, 2022)
Speech that uses words that are not grammatically related to parts of speech is also used in speech. Such words are semantically related to the whole sentence or to a part of it . These are : motivation , preposition , preposition and preposition. Such units do not accept syntactic connections , ie they are not syntactically related to other parts of speech